Angiomiolipoma renal. - Zegarra, Luis; Medina, Raúl; Melgarejo, Weymar; Salinas, César (Revista Médica Herediana, 2013)
We report a fifty three years old female patient, who suffered right lumbar pain, total hematuria and palpable abdominal mass. An abdominal T.A.C. showed a right renal tumor of fat density. Renal Angiomiolipoma an teratoma were considered among neoformative processes. It wasn’t found any tumor´s extension. Radical nefrectomy was done. The histopatologic diagnosis was renal angiomiolipoma